Documentation of ethnoveterinary knowledge: Harnessing potential phytotherapy in high mountainous areas of Paddar, District Kishtwar (India) - Singh, Kanwaljeet; Kumar, Bushan; Kumar, Pankaj; Lone, Javaid Fayaz; Sharma, Yash Pal; Gairola, Sumeet (Ethnobotany Research and Applications, 2022)
Background: Most people and livestock producers in rural India continue to rely on traditional medicine for health-care practices. The aim of the present study was to document important plant species employed by the people of Paddar to treat livestock ailments. Methods: Reconnaissance surveys were conducted in Paddar from April 2020 to September 2021. A total of 65 informants (37 men and 28 women) were interviewed during the period. Ethnoveterinary data was collected employing semi-structured interviews and participatory observations. The data were analyzed using frequency of citation (FC) and Informant consensus factor (FIC). Results: In total, 43 plant species were used to treat 11 livestock diseases. Herbs were the leading growth forms and leaves were the most used parts used for the treatment purposes. Powder form was the main herbal preparation, and the oral route was the main administration mode. Aucklandia costus, Skimmia laureola, Picrorhiza kurroa, Rumex nepalensis, and Betula utilis were the frequently cited plant species. The FIC value for disease categories ranged from 0.93 to 1. Fourteen plant species were used to treat gastrointestinal disorders. Conclusion: The present study is conducted for the first time in the region. Novel uses were reported for Achillea millefolium, Berberis lycium, Ototropis elegans, Desmostachya bipinnata, Lablab purpureus, Rheum webbianum, and Aucklandia costus. These species should be the focus of phytochemical and pharmacological investigation, which might lead to the creation of more effective veterinary drugs. Key words: Livestock disease, Traditional knowledge, Plant resources, Paddar, Jammu and Kashmir